2023
DOI: 10.1021/acs.inorgchem.3c02389
|View full text |Cite
|
Sign up to set email alerts
|

Ample Lewis Acidic Sites in Mg2B2O5 Facilitate N2 Electroreduction through Bonding–Antibonding Interactions

Ashmita Biswas,
Bikram Ghosh,
Kathi Sudarshan
et al.

Abstract: Extensive research on the electrochemical nitrogen reduction reaction (NRR) has put forward a sound list of potential catalyst materials with properties inducing N2 adsorption, protonation, and reduction. However, rather than a random selection of catalysts, it is essential to understand the vitals in terms of orbital orientation and charge distribution that actually manipulate the rate-determining steps of NRR. Realizing these factors, herein we have explored a main group earth-abundant Mg-based electrocataly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Then, their linear regression plots were made between the scan rate and Δ j (difference of anodic and cathodic current densities) obtained from the cyclic voltammetry (CV) curves to get a straight line by fitting with slope, giving rise to the double-layer capacitance ( C dl ) value, as shown in Figure c. Next, electrochemically active surface area (ECSA) was calculated using eq S2 in the SI, and it was found that ECSA in the case of the N 2 medium was less as compared to in the Ar medium presented by the bar plot in Figure d. This result suggested that more active sites were occupied with N 2 on ZAO, leading to lower ECSA in N 2 as compared to Ar.…”
Section: Resultsmentioning
confidence: 99%
“…Then, their linear regression plots were made between the scan rate and Δ j (difference of anodic and cathodic current densities) obtained from the cyclic voltammetry (CV) curves to get a straight line by fitting with slope, giving rise to the double-layer capacitance ( C dl ) value, as shown in Figure c. Next, electrochemically active surface area (ECSA) was calculated using eq S2 in the SI, and it was found that ECSA in the case of the N 2 medium was less as compared to in the Ar medium presented by the bar plot in Figure d. This result suggested that more active sites were occupied with N 2 on ZAO, leading to lower ECSA in N 2 as compared to Ar.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the fossil fuel depletion as well as the environmental pollution it is inevitable to search for alternative renewable energy sources. 1,2 Hydrogen production from water splitting is a clean and sustainable approach for solving the problem. [2][3][4][5] Electrochemical water splitting is one of the most efficient ways for hydrogen production for the sustainable energy.…”
Section: Introductionmentioning
confidence: 99%